Association of Elevated ASO Titer with Plaque and Guttate Psoriasis - Rakhi Kumari, Sorath Sohail, Samrin Dost, Syeda Shahmoona Tirmizi, Sana Siddiqui, Fozia Shaikh, (Pakistan Journal of Medical & Health Sciences, 2022)
Objectives: To determine the association of elevated ASO titer with plaque and guttate psoriasis. Study Design: Case control study. Place and Duration: Department of Dermatology, Shaheed Mohtrama Benazir Bhutto Medical University (SMBBMU), Larkana during from 22nd January 2018 to 21st July 2018 Materials & Methods: A total of 30 patients with plaque or guttate psoriasis and 30 controls, 20 to 60 years of age of either gender were included. Patients taking systemic anti-psoriatic drugs, CRF and erythroderma were excluded. After this throat swabs were taken and pathogenic organism was identified by gross colony morphology and types of hemolysis on culture media. β-hemolysis indicated growth of Streptococcus pyogens. Antistreptolysin O titer (ASO titer) was measured and titer >200 IU/ml was taken as elevated. Results: Mean age was 40.92 ± 10.62 years. Out of 60 patients, 40 (66.67%) were males and 20 (33.33%) were females with male to female ratio of 2:1. Frequency of elevated ASO titer in patients with plaque and guttate psoriasis was found in 13 (43.33%) and in 04 (13.33%) controls with p-value of 0.014 and odds ratio of 2.97. Conclusion: This study concluded that concluded that there is positive association of elevated ASO titer with plaque and guttate psoriasis. Keywords: Psoriasis, Throat Infection, ASO Titer